The neighborhood bench, designed with the neighborhood: a participatory design-build project - Titus, August (Kansas State University, 2021)
The placement of street furniture, especially benches, can help shape and activate public space. Outdoor benches and other street furniture can contribute to a neighborhood’s “urban identity” (van Uffelen 2010). However, mass production of street furniture over the past century has led to a basic, near universal design style for benches (Olin 2017). Yet, a bench, like public art, can be designed to tell a story and reflect a neighborhood’s unique character and visual identity. Thus, this project asks, how can a participatory design-build process inform the design and fabrication of a custom bench for a neighborhood? To inform the development of the participatory design-build process, the Ivanhoe neighborhood, in Kansas City, Missouri, was selected as the focus site. In working with a focus group of neighborhood residents, three participatory workshops were held to inform the design of a custom bench to be located in Jim Nutter Park. The workshops were collaborative sessions where participants expressed their thoughts and stories about their neighborhood; provided guidance and feedback and on preliminary design concepts; and expressed opinions about design details including overall size, materials, and colors. Guided by this feedback, a custom bench was fully designed and fabricated to reflect the focus groups’ ideas. Reflecting on the overall process, a replicable participatory design-build guide was then developed for use by other designers, artisans, and craftspeople in future custom bench projects.
Keywords: Participatory design; Bench design; Outdoor seating; Street furniture; Bench fabrication